The Influence on Sustainability Report Quality toward Financial Performance - Wijaya Triwacananingrum; Chelsy Cyndy Limpele (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
The purpose of this research is to see if the quality of a sustainability report has an effect on firm’s performance. The quality of sustainability report is assessed by its assurance statement and also from the disclosure of GRI standards on the sustainability report. The samples that are used for this research are the firms who had received the ASRRAT award for 2018-2020 period which will be using the reports from 2017-2019. The result of this research shows that the variables used such as sustainability disclosure index and assurance statement has no effect on firm’s performance but then again when both of the variables are tested simultaneously result shows that it has a positive effect on firm performance which on this research is measured by return on assets. But the variable firm size is proven to have a negative effect on firm’s performance and industry sensitivity is proven to have no effect on firm’s performance.